Sudden death in young competitive athletes. Clinical, demographic, and pathological profiles - Maron, B. J.; Shirani, J.; Poliac, L. C.; Mathenge, R.; Roberts, W. C.; Müller, F. O. (Journal of the American Medical Association, 1996)
OBJECTIVE: To develop clinical, demographic, and pathological profiles of young competitive athletes who died suddenly. DESIGN: Systematic evaluation of clinical information and circumstances associated with sudden deaths; interviews with family members, witnesses, and coaches; and analyses of postmortem anatomic, microscopic, and toxicologic data. PARTICIPANTS AND SETTING: A total of 158 sudden deaths that occurred in trained athletes throughout the United States from 1985 through 1995 were analyzed. MAIN OUTCOME MEASURES--Characteristics and probable cause of death. RESULTS: Of 158 sudden deaths among athletes, 24 (15%) were explained by noncardiovascular causes. Among the 134 athletes who had cardiovascular causes of sudden death, the median age was 17 years (range, 12-40 years), 120 (90%) were male, 70 (52%) were white, and 59 (44%) were black. The most common competitive sports involved were basketball (47 cases) and football (45 cases), together accounting for 68% of sudden deaths. A total of 121 athletes (90%) collapsed during or immediately after a training session (78 cases) or a formal athletic contest (43 cases), with 80 deaths (63%) occurring between 3 PM and 9 PM. The most common structural cardiovascular diseases identified at autopsy as the primary cause of death were hypertrophic cardiomyopathy (48 athletes [36%]), which was disproportionately prevalent in black athletes compared with white athletes (48% vs 26% of deaths; P = .01), and malformations involving anomalous coronary artery origin (17 athletes [13%]). Of 115 athletes who had a standard preparticipation medical evaluation, only 4 (3%) were suspected of having cardiovascular disease, and the cardiovascular abnormality responsible for sudden death was correctly identified in only 1 athlete (0.9%). CONCLUSIONS: Sudden death in young competitive athletes usually is precipitated by physical activity and may be due to a heterogeneous spectrum of cardiovascular disease, most commonly hypertrophic cardiomyopathy. Preparticipation screening appeared to be of limited value in identification of underlying cardiovascular abnormalities.